Fixatives increase the efficacy of gel formulations containing Piper aduncum linnaeus (Piperales: Piperaceae) essential oil as repellenty - Hidayatulfathi Othman; Mamood S. N. H.; Kalaivany M.; Budin S. B.; Ahmad Rohi Ghazali; Zulfakar M. H. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Piper aduncum essential oil exhibit repellency activity and has a potential to be use as an alternative for synthetic repellent such as N,N-diethyl-3- methylbenzamide, (DEET). However, the volatility properties of the essential oil decrease their persistence as a topical repellent. Study has shown that formulation of the essential oil with some fixatives may increase their effectiveness. Therefore, this study was conduct to evaluate the effectiveness of gel formulation containing P. aduncum essential oil with two fixative; vanillin and paraffin oil. Gel formulations containing P. aduncum essential oil with 5% and 10% vanillin and 6% paraffin oil was prepared and tested against Aedes aegypti in laboratory using Standards and Industrial Research Institute of Malaysia (SIRIM) bioassay method. After 240 minute post-application, formulation containing 5% and 10% vanillin was able to provide >70% repellency percentage against mosquito while formulation containing 6% paraffin oil gives <30% repellency percentage. As conclusion, P. aduncum based repellent gel containing 5% and 10% vanillin was able to prolong the effect of P. aduncum essential oil as repellent against dengue vector in laboratory.